Financial Sector Assessment Program Update : Republic of Poland - Competition and Performance in the Polish Second Pillar - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
In March 1999, Poland implemented a systemic pension reform that involved the introduction of a multi-pillar pension system to replace the defined benefit (DB), pay-as-you-go (PAYG) system that had been operating since 1949. This technical note on the pension sector was elaborated as part of the Poland Financial Sector Assessment Program, or FSAP update that took place in April-May 2006. The note assesses the structure and performance of the second pillar, as well as its regulatory and supervisory framework. The note is structured as follows. Section two provides an overview of the whole pension system after the 1999 reform, including coverage and fiscal policy in the transition to the new system. Section three analyses the structure and performance of the second pillar, including asset growth, portfolio composition, investment returns, and fees. Section four examines the regulatory and supervisory framework for the second pillar. Section five analyzes briefly the status of capital market development and the main obstacles to the further development of financial instruments suitable to pension funds. Finally, section six provides a number of policy recommendations.